Documentation of Pharmaceutical Development. Part 1. Study of the Documentation of the Site - I. E. Smekhova; L. V. Shigarova; V. D. Meteleva; E. V. Flisyuk (Разработка и регистрация лекарственных средств, 2021)
Introduction. The trends in the modern pharmaceutical industry demonstrate the need for proper documentation of all stages of the life cycle of a medicinal product to ensure its quality and eliminate risks to patients. Therefore, documenting pharmaceutical development, as the first stage of this cycle, is relevant. It will allow regulating technological processes, product quality indicators, as well as ensuring the integrity of the data received. It is advisable to document the pharmaceutical development taking into account the requirements established at the enterprise where the industrial production of this drug is planned.Aim. Development of documentation for pharmaceutical development within the pharmaceutical quality system of the enterprise. One of the objectives of the study was to analyze the document flow of the pharmaceutical quality system of the enterprise planning the production of suppositories for the proper development of documentation for the pharmaceutical development of a medicinal product in this dosage form.Materials and methods. During the research the following methods were used: content analysis; system analysis; sociological (survey method); SWOT analysis technology; systems approach.Results and discussion. In order to get acquainted with modern trends related to pharmaceutical development and pharmaceutical quality system, at the first stage, an analysis of the ICH (International Council on Harmonization) guidance document Quality Implementation Working Group on Q8, Q9 and Q10 Questions & Answers was carried out. An important preparatory stage for the optimal documentation of a pharmaceutical development was the study of the document flow of the pharmaceutical quality system of an enterprise planning to produce two-component suppositories. For this purpose, in the course of the research, a questionnaire was developed containing questions related to the functioning of the quality system, documentation processes and production. The analysis of the received responses made it possible to obtain information on documenting the pharmaceutical development of medicinal products, as well as to identify the main trends associated with this process within the pharmaceutical quality system.Conclusion. The documentation of the pharmaceutical quality system of the enterprise planning the production of suppositories has been analyzed. The strengths and weaknesses of the documentation are identified, a number of proposals for improving the documentation system are highlighted. Based on the results obtained, proposals will be developed for the optimal documentation of pharmaceutical development and a set of documents for an enterprise planning to produce two-component suppositories will be formed.